"Bullets and barter": The force of love speech in Jeanette Winterson's Written on the Body. Issue 4 (8th August 2018) - Jacobs, Courtney
ABSTRACT: Building on the foundational work of J. L. Austin, Jacques Derrida, and Judith Butler, this article investigates declarations of love as promissory speech acts that carry a daunting force. As its title suggests, Jeanette Winterson's experimental novel Written on the Body explores the relationship between language, convention, and materiality that speech act theory also catalogs, yet the text's elusive romance invites readers to question the sacrosanct linguistic customs that dictate love speech. Comparable to hate speech in its ability to engender uncertainty and vulnerability, the force of love speech, as imagined by Winterson, nevertheless supersedes any statement made in description of, or contract "written upon, " the physical form, and rather transcends the traditional opposition between constative and performative utterance. Through an analysis of Winterson's literary lovers, this article locates the force of love speech in the collapse of the distinction between word and action, between the linguistic and the material.